The protective effect of carbamazepine on acute lung injury induced by hemorrhagic shock and resuscitation in rats. - Yaqiang Li; Hiroko Shimizu; Ryu Nakamura; Yifu Lu; Risa Sakamoto; Emiko Omori; Toru Takahashi; Hiroshi Morimatsu (PLoS ONE)
Hemorrhagic shock and resuscitation (HSR) enhances the risk of acute lung injury (ALI). This study investigated the protective effect of carbamazepine (CBZ) on HSR-induced ALI in rats. Male Sprague-Dawley rats were allocated into five distinct groups through randomization: control (SHAM), saline + HSR (HSR), CBZ + HSR (CBZ/HSR), dimethyl sulfoxide (DMSO) + HSR (DMSO/HSR), and CBZ + chloroquine (CQ) + HSR (CBZ/CQ/HSR). Subsequently, HSR models were established. To detect tissue damage, we measured lung histological changes, lung injury scores, and wet/dry weight ratios. We measured neutrophil counts as well as assessed the expression of inflammatory factors using RT-PCR to determine the inflammatory response. We detected autophagy-related proteins LC3II/LC3I, P62, Beclin-1, and Atg12-Atg5 using western blotting. Pretreatment with CBZ improved histopathological changes in the lungs and reduced lung injury scores. The CBZ pretreatment group exhibited significantly reduced lung wet/dry weight ratio, neutrophil aggregation and number, and inflammation factor (TNF-α and iNOS) expression. CBZ changed the expression levels of autophagy-related proteins (LC3II/LC3I, beclin-1, Atg12-Atg5, and P62), suggesting autophagy activation. However, after injecting CQ, an autophagy inhibitor, the beneficial effects of CBZ were reversed. Taken together, CBZ pretreatment improved HSR-induced ALI by suppressing inflammation, at least in part, through activating autophagy. Thus, our study offers a novel perspective for treating HSR-induced ALI.